Pengaruh Kepemimpinan dan Budaya Kerja terhadap Kinerja Pegawai pada Satpol PP Kabupaten Solok - Putra, Riyosnal; Dasril, Mience; Syafwandi, Syafwandi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of leadership and work culture on employee performance at the Civil Service Police Unit (Satpol PP) in Solok Regency. The research method used is quantitative with a survey approach using a questionnaire. The number of respondents was 73 Satpol PP employees. Data analysis was carried out in several stages, namely 1) Validity test was tested with Pearson correlation (r count > r table). 2) Reliability was tested with Cronbach Alpha (> 0.60 is considered reliable). 3) Normality test to determine whether the data is normally distributed or not 4) T test to determine the effect of each independent variable on the dependent variable. 5) F test to determine the effect of leadership and work culture simultaneously on employee performance. 6) Coefficient of Determination (R²) to determine how much the independent variable contributes to explaining the dependent variable. Effective leadership, shown by exemplary attitudes, open communication, and participatory decision-making, as well as a conducive work culture such as discipline, responsibility, and teamwork, has been proven to be able to increase employee productivity and work quality. This research provides theoretical and practical contributions in efforts to improve the performance of local government apparatus.